Case Report: Occlusion of the foramen of Monro treated with endoscopic septostomy and foraminotomy in a preterm neonate - Lai, Po-Yu; Li, Cheng-Hao; Yang, Ming-Tao; Feng, Pao-Hui; Kuok, Chi-Man (Frontiers in Surgery, 2023)
Background: Hydrocephalus is a brain abnormality frequently encountered in neonates. There are several known etiologies of hydrocephalus, which can be classified as either congenital or acquired. Occlusion of the foramen of Monro (FOM) is a cause of hydrocephalus and can be either congenital or secondary to various disorders. Idiopathic obstruction of the FOM presenting as prenatal ventriculomegaly is extremely rare but has been reported. Case presentation: We present the case of a preterm newborn with severe bilateral hydrocephalus due to FOM occlusion in the prenatal period. Although the neonate had normal head circumference and no clinical symptoms after birth, brain sonography revealed progressive ventriculomegaly. Further image revealed bilateral ventriculomegaly with normal-sized third and fourth ventricles. We suspected a complete obstruction of the right and a partial obstruction of the left of the FOM. The neonate underwent endoscopic septostomy and foraminotomy, resulting in improvement. Conclusion: We report a case of preterm FOM occlusion in the youngest and smallest neonate to date. Endoscopic septostomy and foraminotomy were performed in order to avoid ventriculoperitoneal shunt-related complications, highlighting the viability of endoscopic procedures which should be the primary treatment in preterm neonates with FOM occlusion.